PROJEK CERIA: STUDI KASUS PENINGKATAN PENALARAN MORAL MELALUI DILEMA MORAL DAN KARTU KARAKTER DI SEKOLAH DASAR - Indri Apriyani; Wildan Nurul Fajar (STKIP Subang, 2026)
Character education in elementary schools tends to emphasize moral action through habituation and external reinforcement, while neglecting moral knowing and moral feeling, so that students' moral reasoning remains dominated by punishment- and reward-based motives and rarely develops into autonomous, internalized values; this condition is worsened by the weak collaborative bridge between schools and families, as reflected in the low proportion of parents who consistently monitor their children's character development at home. This study aims to describe qualitatively the design, implementation, obstacles, and impact of PROJEK CERIA (Cerdas Moral, Empati, Refleksi, Integritas, Aksi), a teacher-initiated character program implemented in Class 6A of SD Negeri Patimuan 01, Cilacap Regency, which integrates weekly moral dilemma discussions with the CERIA Card as a daily school-home character monitoring instrument. A qualitative descriptive approach with a single case study design was employed, involving 20 students and their parents as participants, with data collected through moral reasoning interviews, observation, document analysis, and focus group discussions, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the program successfully shifted students' moral reasoning from punishment- and reward-based motives toward empathy- and universal-principle-based reasoning, increased spontaneous moral initiative without supervision, and fostered parental ownership of character education at home, despite technical, pedagogical, and parental collaboration obstacles that were addressed through contextual, low-cost strategies. The study concludes that simple, well-designed instruments can effectively bridge school and home character education even in resource-limited rural settings.